The influence of historical climate cycles on the diversification and demography of species from the Neotropical lizard group Anolis chrysolepis - Vieira de Oliveira, Ana Paula; D’Angiolella, Annelise; Azevedo, Josué Anderson R.; Vitt, Laurie J.; Colli, Guarino R.; Choueri, Erik L.; Gamble, Tony; Taucci, Pedro P. G. [UNESP]; Rodrigues, Miguel T.; Noonan, Brice P.; Avila-Pires, Teresa C.; Werneck, Fernanda P. (Oxford University Press (OUP), 2025)
Historical shifts in climate have significantly influenced the establishment of ecosystems and the evolution of species. Phylogeographical studies integrated with niche modelling can provide insights into divergence events and demography. This study explores the evolutionary history, demographic patterns, and spatiotemporal dynamics of seven South American lizard species of the Anolis chrysolepis species group, which has been proposed to be strongly impacted by Pleistocene climatic fluctuations under the Refugia Hypothesis. We utilized mitochondrial and nuclear DNA sequences to delineate lineages, estimate divergence times, and examine demographic dynamics. Ecological niche models were employed to assess historical range shifts and identify climatic stability zones during the Quaternary. Our results identified 40 distinct lineages within the group. The species A. chrysolepis and A. tandai exhibited the highest lineage diversity, with seven and 12 lineages, respectively, while others showed fewer divergences. In the Cerrado savannas, species diversification aligns with Miocene geological and climatic changes, supporting the plateau/depression theory. In Amazonia, diversification during the Miocene was tied to Andean orogenesis, with Pleistocene range expansions influenced by climatic cycles. All species demonstrated demographic declines during the Pleistocene. Niche models highlighted stability areas in the Cerrado, and western and northern Amazonia, consistent with proposed refugia. These findings offer new insights into the biogeographical and evolutionary processes shaping biodiversity in these megadiverse regions.
Keywords: Amazonia; anoles lizards; Cerrado; phylogeography; population dynamics; spatiotemporal reconstruction